Reflective Story on Diversity and Inclusive Education - Dahal, Hikmat (NPRC Journal of Multidisciplinary Research, 2024)
This reflective article explores the current scenario of diversity and inclusion through the narration of a deaf ethnic child. Self-reflection is taken as an instrument for behavioural modification since the author is aware of its significance in education. This study aims to explore the experiences and implementation of inclusive education through the author's personal teaching experiences. The article employs a reflective narration of the author working as a novice teacher in a school exercising to incorporate deaf children into mainstream courses. The emphasis is on Krishna, a Dalit youngster with hearing difficulties, who had challenges in adaptation owing to cultural, social and educational obstacles. The results showed the obstacles encountered by such children who had to face social isolation, communication obstacles and insufficient educator training. The author's intervention in Krishna's metamorphosis underscores the necessity of helpful learning environments. The article links Krishna's experiences to wider socio-economic and cultural challenges, indicating that inclusive education is necessary for structural reforms in teacher training, cultural sensitivity and familial support. The results underscore the necessity of embracing diversity and enacting effective inclusive education policies to cultivate equal learning environments for all children.